186 - SELF-MEDICATION AND POLYPHARMACY THE ELDERLY (Fiep Bulletin - online, 2011)
Self-medication is a common practice, however, can allow masking problems and diseases, drug interactions and poisonings. The aim of this study was to identify the prevalence of drug in the elderly population. We conducted a cross-sectional study with 20 subjects. It was found that drugs used in medical prescriptions, are acquired and UBS in the neighborhoods where the elderly die. It was observed that the most common diseases that motivate self-medication were headache, cough, flu and colds. The data indicate the need for interventions with the population, and to have insight into their social situation, their physical and biological. We conclude there is a need for continuing education of health professionals to prescribe rational prevention of possible injuries caused by inadequate consumption of medicines. In addition to public policies to curb the sale and use of unnecessary medications, enforcing sanitary legislation in force.
Keywords: self-medication; elderly; rational use of medicines